If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3w + -12 + w) = 640 Reorder the terms: 2(-12 + 3w + w) = 640 Combine like terms: 3w + w = 4w 2(-12 + 4w) = 640 (-12 * 2 + 4w * 2) = 640 (-24 + 8w) = 640 Solving -24 + 8w = 640 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + 8w = 640 + 24 Combine like terms: -24 + 24 = 0 0 + 8w = 640 + 24 8w = 640 + 24 Combine like terms: 640 + 24 = 664 8w = 664 Divide each side by '8'. w = 83 Simplifying w = 83
| -9p=-72 | | 1.96x^5-4x^2-16x-16=0 | | 7-7(1-7x)=8x | | p(x)=-2x+100x-25 | | s-7/10=13/10 | | 12y=13.2 | | 5x+1+3=8(3x+2)+7(2-3x) | | 7(2y+1)=3(7+5y) | | X+x+.11+x+.11+.38=10.32 | | (2x+10)=(2x-15) | | 2(w+20+w)=380 | | -(1+6n)=-152 | | 121=0 | | 18-[2+3(8-5)]= | | 8(2+2x)-6=90 | | (x-2)2+(y+6)2=25 | | 2(x-3)+9=2x+2 | | X+5x+13=140 | | 1/2x=121 | | 19-5x/2=33 | | Y=6(6)-2 | | -x^2+5x+3=0 | | Y=6(4)-2 | | -4z+6x-2y+2z-3y= | | 3x/4x-2-2x/6x-3=5/2x-1 | | 14x+4+18x-4+14x-8=360 | | (6x-9)(3x+4)=0 | | 5/6=x/32 | | x/8=x/9-7 | | 3n-2÷5=7/10 | | f(x+7)=6x+6 | | 20+4-8=4x |